A presença dos soldados da borracha nas páginas do Correio da Manhã (1943-1950) - Gonçalves, Flávia Soraia de Araujo (2024)
This dissertation aims to contextualize how rubber soldiers, rubber tappers and rubber tappers were represented by the newspaper Correio da Manhã during the Second World War. These workers played a key role in the extraction and supply of rubber, a strategic input for the war effort, especially between 1942 and 1950, when Brazil allied with its partners. During the Second World War, rubber production in Brazil played a fundamental role for the allied countries. Rubber tappers, responsible for extracting rubber, faced adverse conditions under the exploitation of rubber tappers, while rubber soldiers dealt with the absence of support. With its local hegemony, coronelismo intensified these inequalities, highlighting the social tensions in rubber production in that period. Being structured in 3 (three) chapters: the first deals with the exploitation of rubber plantations, the second with the Battle of Rubber, and the third analyzes the rubber soldiers in Correio da Manhã, which aims to contribute significantly to a deeper understanding of the history of rubber tappers and rubber tappers, as well as for a critical reflection on the media and social representations of these communities, with the press being a fundamental tool for understanding the interactions between the press and History. The aim is to understand how soldiers' stories influenced public perception of their role and importance by examining the language and topics covered. This analysis will enable a reflection on the social and political dynamics of the time and the role of the media in the construction of collective memory. The dissertation questions how Correio da Manhã represented rubber soldiers between 1943 and 1950, and the consequences of these images for rubber tappers and rubber tappers. The dissertation will explore how the newspaper helped to build the image of rubber soldiers, using sources such as the Hemeroteca Digital Brasileira.